2018
DOI: 10.1007/s00059-018-4691-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and collateral circulation in acute ischemic stroke

Abstract: The development of collateral circulation in patients with acute ischemic stroke with ICA occlusion may be influenced by BP. A moderately decreased SBP is associated with good integrity of the collateral circulation in patients with acute ischemic stroke with occlusion of the ICA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…However, the relationship between baseline BP and CC has been barely described. One study of AIS patients treated with intravenous thrombolytic therapy (with or without LVO) found that moderately elevated systolic BP was associated with good CC but with an inverse association of systolic BP and 3-month clinical outcome ( 8 ); another study found that lower systolic BP was associated with good CC but in patients with ICA occlusion during the first 3 days from stroke onset ( 9 ). In this regard, our study adds relevant information confirming that both systolic BP and mean BP at admission are inversely associated with the CS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between baseline BP and CC has been barely described. One study of AIS patients treated with intravenous thrombolytic therapy (with or without LVO) found that moderately elevated systolic BP was associated with good CC but with an inverse association of systolic BP and 3-month clinical outcome ( 8 ); another study found that lower systolic BP was associated with good CC but in patients with ICA occlusion during the first 3 days from stroke onset ( 9 ). In this regard, our study adds relevant information confirming that both systolic BP and mean BP at admission are inversely associated with the CS.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, a higher admission blood pressure (BP) ( 6 ) and BP drops during EVT ( 7 ) are associated with a poorer clinical outcome after EVT. However, there are scarce and contradictory data evaluating the effect of admission BP on CC in AIS ( 8 , 9 ). A better understanding of this relationship could lead to an optimisation of CC by a better management of pre-procedural and intra-procedural BP.…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography and quantitative susceptibility mapping (QSM) studies have confirmed the existence of this compensatory process ( 49 - 52 ). In addition, the collateral circulation pathway in the brain gradually opens, providing an alternative vascular pathway for ischemic tissue ( 53 , 54 ). In stage II, the body’s reserve capacity is exhausted, and the ischemic tissue shows metabolic alterations and changes in pH.…”
Section: Discussionmentioning
confidence: 99%
“…Collateral circulation was scored as intermediate (ASITN grade: 2). 4 Through a tri-axial system, a reperfusion catheter (ACE 68, Penumbra, Alameda, CA) was brought in contact with the clot in 10 minutes. At the moment of the withdrawal of the thrombus-aspiration system, the clot was found neither in the aspiration pump nor in the reperfusion catheter.…”
Section: Acute Phase Managementmentioning
confidence: 99%